Duration of Heart Failure With Reduced Ejection Fraction Associated With Electrocardiographic Outcomes Before and After Sacubitril/Valsartan - Po-Lin Lin MD; Ying-Hsiang Lee MD; Lawrence Yu-Min Liu MD, PhD; Cheng-Ting Tsai MD; Ten-Fang Yang MD; Wei-Ru Chiou MD; Mu-Yang Hsieh MD; Hung-Yu Chang MD; Chun-Che Huang PhD (SAGE Publishing, 2022)
Aim: Changes in QRS duration in patients with heart failure with reduced ejection fraction (HFrEF) after sacubitril/valsartan therapy is not fully understood. This study aimed to assess the association of duration of HFrEF diagnosis with electrocardiographic and echocardiographic outcomes between before and after sacubitril/valsartan. Methods: We included HFrEF patients who received naïve sacubitril/valsartan therapy for ≥3 months, between January 2016 and March 2018. All patients were divided into 2 groups based on their duration of HFrEF. Generalized linear models were analyzed the cardiac outcomes after sacubitril/valsartan therapy by HFrEF duration. Results: Among these, 42 patients were HFrEF duration of <1 year and 47 patients were ≥1 year. The mean difference of QRS duration was lesser in the <1-year group than in the ≥1-year group (−2.3 msec vs 6.3 msec; P = .029). However, the mean difference of left ventricular ejection fraction (LVEF) was higher in the ≥1-year group (13.8% vs 5.8%; P = .008). After adjusting for patient demographics and clinical characteristics, the ≥1-year group had a significantly prolonged QRS duration (coefficient = 11; 95% confidence interval [CI], 0.3-21.7) and an unfavorable LVEF recovery (coefficient = −10.3; 95% CI −14.5 to −6.1) compared with the <1-year group. Conclusion: Prolonged QRS durations and unfavorable LVEF recoveries after sacubitril/valsartan therapy were observed in patients with HFrEF duration of ≥1 year. Earlier diagnosis of HFrEF and appropriate medication treatment may be beneficial in the improvement of QRS duration and LVEF recovery.